A literature review of the gender-differentiated impacts of climate change on women's and men's assets and well-being in developing countries - Goh, Amelia H. X. (International Food Policy Research Institute, 2012)
Climate change increasingly affects the livelihoods of people, and poor people experience especially negative impacts given their lack of capacity to prepare for and cope with the effects of a changing climate. Among poor people, women and men may experience these impacts differently. This review presents and tests two hypotheses on the gender-differentiated impacts of climate change on women and men in developing countries. The first hypothesis is that climate-related events affect men’s and women’s well-being and assets differently. The second hypothesis is that climate-related shocks affect women more negatively than men. With limited evidence from developing countries, this review shows that climate change affects women’s and men’s assets and well-being differently in six impact areas: (i) impacts related to agricultural production, (ii) food security, (iii) health, (iv) water and energy resources, (v) climate-induced migration and conflict, and (vi) climate-related natural disasters. In the literature reviewed, women seem to suffer more negative impacts of climate change in terms of their assets and well-being because of social and cultural norms regarding gender roles and their lack of access to and control of assets, although there are some exceptions. Empirical evidence in this area is limited, patchy, varied, and highly contextual in nature, which makes it difficult to draw strong conclusions. Findings here are indicative of the complexities in the field of gender and climate change, and signal that multidisciplinary research is needed to further enhance the knowledge base on the differential climate impacts on women’s and men’s assets and well-being in agricultural and rural settings, and to understand what mechanisms work best to help women and men in poor communities become more climate resilient.